Effect of heat treatment on diffusion, internal friction, microstructure and mechanical properties of ultra-fine-grained nickel severely deformed by equal-channel angular pressing. (1st January 2015) - Divinski, Sergiy V.; Reglitz, Gerrit; Golovin, Igor S.; Peterlechner, Martin; Lapovok, Rimma; Estrin, Yuri; Wilde, Gerhard
Abstract: Severe plastic deformation via equal-channel angular pressing was shown to induce characteristic ultra-fast diffusion paths in Ni (Divinski et al., 2011). The effect of heat treatment on these paths, which were found to be represented by deformation-modified general high-angle grain boundaries (GBs), is investigated by accurate radiotracer self-diffusion measurements applying the 63 Ni isotope. Redistribution of free volume and segregation of residual impurities caused by the heat treatment triggers relaxation of the diffusion paths. A correlation between the GB diffusion kinetics, internal friction, microstructure evolution and microhardness changes is established and analyzed in detail. A phenomenological model of diffusion enhancement in deformation-modified GBs is proposed.